The 2020 Eruption and Large Lateral Dike Emplacement at Taal Volcano, Philippines: Insights From Satellite Radar Data. Issue 7 (29th March 2021) - Bato, M. G.; Lundgren, P.; Pinel, V.; Solidum, R.; Daag, A.; Cahulogan, M.
Abstract: On January 12, 2020, Taal volcano, Philippines, erupted after 43 years of repose, affecting more than 500, 000 people. Using interferometric synthetic aperture radar (InSAR) data, we present the pre‐ to post‐eruption analyses of the deformation of Taal. We find that: (1) prior to eruption, the volcano experienced long‐term deflation followed by short‐term inflation, reflecting the depressurization‐pressurization of its ∼5 km depth magma reservoir; (2) during the eruption, the magma reservoir lost a volume of 0.531 ± 0.004 km 3 while a 0.643 ± 0.001 km 3 lateral dike was emplaced; and (3) post‐eruption analyses reveal that the magma reservoir started recovery approximately 3 weeks after the main eruptive phase. We propose a conceptual analysis explaining the eruption and address why, despite the large volume of magma emplaced, the dike remained at depth. We also report the unique and significant contribution of InSAR data during the peak of the crisis. Plain Language Summary: Taal volcano in the Philippines erupted on January 12, 2020. Here, we present the pre‐, co‐, and post‐eruption data, model, and analyses using interferometric synthetic aperture radar (InSAR) data acquired by various satellite systems. We find that: (1) prior to the eruption, the volcano experiences a sequence of long‐term (>1 year) deflation followed by short‐term (≤1 year) inflation as a result of the depressurization‐pressurization of its ∼5 km depth magma reservoir; (2) during the eruption, the magma reservoir lost a volume of 0.531 ± 0.004 km 3 while a 0.643 ± 0.001 km 3 lateral dike was emplaced; and (3) post‐eruption analyses reveal that the magma reservoir is in recovery starting ∼3 weeks after the main eruptive phase. We propose a conceptual analysis to explain the 2020 Taal eruption and the dike emplacement. We also report the unique and significant contribution of remote sensing data, particularly InSAR during the peak of the crisis. Key Points: We present a comprehensive interferometric synthetic aperture radar (InSAR)‐based data, analyses, and models of Taal's pre‐ to post‐eruptive state During the eruptive crisis, Taal's magma reservoir lost 0.531 ± 0.004 km 3 of volume while a 0.643 ± 0.001 km 3 lateral dike was emplaced Low‐latency InSAR‐derived products provided crucial and significant information to PHIVOLCS during the January 2020 eruptive event